Methods of Examination of Patients with Damaged Mucous Floor of the Oral Cavity - Madrakhimova Muslima Mirzokhid qizi (Zien Journals, 2023)
In this article, injuries occurring on the mucous membrane of the oral cavity - morphological elements, methods of examination of patients with damage to the mucous membrane of the oral cavity, the level of intelligence of medical personnel, the mental state of the patient taking into account the diagnosis of the disease and during direct questioning with the patient, instructions were given on the formation of the skills to gain superiority in the diagnosis by studying the patient's lifestyle.
Keywords: Communication; diagnosis; method; disease